2021
DOI: 10.23887/jp2.v4i1.33607
|View full text |Cite
|
Sign up to set email alerts
|

Komparasi Pengaruh Efikasi Diri, Kebiasaan Belajar dan Lingkungan Sekolah Terhadap Hasil Belajar Matematika Siswa SMK

Abstract: Hasil belajar siswa pada pelajaran matematika kelas XI masih banyak yang belum mencapai KKM karen dianggap paling sulit oleh siswa. Jenis penelitian adalah kuantitatif dengan pendekatan korelasional. Subjek penelitian ini adalah seluruh siswa kelas XI di SMKN 2 Gunung Talang sebanyak 34 siswa, SMKN 1 Gunung Talang sebanyak 25 siswa dan SMKN 1 Bukit Sundi sebanyak 48 siswa yang total subjek penelitian yang digunakan adalah 107 orang siswa. Instrumen pengumpulan data menggunakan kuisioner. Teknik analisis data d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…Students with good study habits are able to accept the learning given by the teacher, are able to do their assignments diligently, are able to manage their time when studying, are responsible for their assignments, and always try to do their assignments well. (Agustiningtyas & Surjanti, 2021;Hardimansyah et al, 2021). The third finding shows that at a significance level of 5% with dk = 130, rtable = 0.171, thus rcount = 0.831 > rtable = 0.171, which means that the coefficient value is significant, which means that the correlation between self-efficacy and study habits together on Mathematics knowledge has positive relationship.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Students with good study habits are able to accept the learning given by the teacher, are able to do their assignments diligently, are able to manage their time when studying, are responsible for their assignments, and always try to do their assignments well. (Agustiningtyas & Surjanti, 2021;Hardimansyah et al, 2021). The third finding shows that at a significance level of 5% with dk = 130, rtable = 0.171, thus rcount = 0.831 > rtable = 0.171, which means that the coefficient value is significant, which means that the correlation between self-efficacy and study habits together on Mathematics knowledge has positive relationship.…”
Section: Discussionmentioning
confidence: 82%
“…(Nainggolan et al, 2022;Widiati et al, 2022).A person with good study habits can have a good impact on the development of his or her learning achievements. Several studies that have been conducted previously revealed that study habits simultaneously have a significant effect on student learning achievement (Andrie et al, 2019).Other research results reveal that self-efficacy, study habits and school environment influence vocational school students' mathematics learning outcomes (Hardimansyah et al, 2021). The results of further research also revealed that there was an influence on students' self-efficacy and mathematics learning outcomes (Hartati et al, 2021).Based on several research results, it can be said that self-efficacy and study habits have a significant effect on improving student mathematics learning outcomes.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation